Highly Efficient Water Oxidation Photoanode Made of Surface Modified LaTiO2N Particles. Issue 39 (24th August 2016) - Akiyama, Seiji; Nakabayashi, Mamiko; Shibata, Naoya; Minegishi, Tsutomu; Asakura, Yusuke; Abdulla‐Al‐Mamun, Md.; Hisatomi, Takashi; Nishiyama, Hiroshi; Katayama, Masao; Yamada, Taro; Domen, Kazunari
Abstract : An improved variation of highly active/durable O2 ‐evolving LaTiO2 N powder‐based photoelectrode has been fabricated by pre‐cleaning the powder with mild polysulfonic acid and by homogeneous deposition of CoO x co‐catalyst aided by microwave annealing. The treatment in aqueous solution of poly(4‐styrene sulfonic acid) results in removal of surface LaTiO2 N layers, forming fine pores in the crystallites. The CoO x co‐catalyst by microwave deposition in Co(NH3 )6 Cl3 /ethylene glycol homogeneously covers the particle surface. The LaTiO2 N powder is fabricated into particle‐transferred electrodes on Ti thin film supported on solid substrate. The modified LaTiO2 N grains on the electrode serve as a highly active O2 ‐evolving photoanode achieving 8.9 mA cm −2 of the photocurrent density at 1.23 V versus reversible hydrogen electrode (RHE) in 0.1m NaOH (pH 13) under solar‐simulator irradiation Airmass 1.5 Global (AM 1.5G). The activity has been much improved, compared with conventional LaTiO2 N treated in mineral acid or with CoO x deposited by impregnation. The new electrode also exhibits better durability in fixed‐potential chronoamperometric tests under AM 1.5G irradiation. Abstract : An improved variation of highly active/durable O2‐ evolving LaTiO2 N powder‐based photoelectrode has been fabricated by pre‐cleaning the powder with mild polysulfonic acid and by homogeneous deposition of CoO x co‐catalyst aided by microwave annealing. Fabricated into particle‐transferred electrodes on Ti, the modified LaTiO2 N serves as a highly active photoanode, achieving 8.9 mA cm −2 of the photocurrent density at 1.23 V versus RHE and longer active periods than those by previous methods.